MAHKOTA GEREJA POHSARANG (Sebuah Pengamatan) - I Wayan Heriyanto (Litbang STFT Widya Sasana Malang, 2015)
In the valley of Mount Wilis, Kediri (village of Pohsarang) there is a beautiful building Catholic church, called “Gereja Pohsarang” built in 1936. It is “unusual” church from my perspective. The church is build with specific and typical model that belongs to Javanese culture with dominant stones over its building. The article depicts my personal observation of the building and its details with theological and catechetical meaning. The builder seems to play a very complex symbolism and catecheticism. “Gereja Pohsarang” remains priceless cultural-religious treasure not just for the Catholics but also for people.